Do Men's and Women's Accounts of Surviving a Stroke Conform to Frank's Narrative Genres?. (December 2013) - France, Emma F.; Hunt, Kate; Dow, Clare; Wyke, Sally
We compared the illness narratives of 9 male and 9 female United Kingdom stroke survivors using Frank's typologies of illness narratives. Most respondents presented a single dominant narrative genre ("quest memoir, " "restitution, " "chaos, " or a new "despair" genre); none presented quest manifesto or automythology narratives of social action or self-reinvention. We found no gender differences apparent in which genres respondents presented. Stroke severity and the degree of anticipated or actual recovery largely influenced which genre predominated in individual accounts. Contrary to some sociological understandings of gender and health, gender appeared to be less influential on stroke survivors' illness accounts than aspects of the illness, such as its severity.